Evaluating the Thermal Performance of Retrofitted Lightweight Green Roofs and Walls in Sydney and Rio de Janeiro. (2017) - Wilkinson, Sara; Feitosa, Renato Castiglia; Kaga, Igor Tsuyoshi; Franceschi, Isabela Hachmann de
Abstract: With increasing densification in urban settlements, environmental issues are a challenge in the sustainable development of all cities globally. Considering that the built environment releases almost half of the total greenhouse gas emissions, an effective solution to mitigating the impacts of increasing temperatures can be the improved performance of existing buildings. Furthermore 87% of the buildings we will have in 2050 are already built. Retrofitting roofs and walls with a living vegetated system such as green roofs and walls could be an upgrade option, increasing sustainable construction. The benefits are improved thermal performance but also improved air quality, stormwater attenuation, increased bio-diversity and lower heating and / or cooling energy consumption. No empirical data exists for Sydney and Rio de Janeiro and the question is; what is the extent of thermal improvement with retrofitted green walls and roof in timber framed and blockwork structures? This study analyses both effects and benefits of the green roofs and walls through an experiment in two countries: one in Sydney, Australia; a timber framed construction, and another one in Rio de Janeiro, Brazil; with blockwork construction. This difference in the material choice was made according to the most common type of construction for housing in each country. In each site, the walls and the roof of one of the prototypes were covered with plants and compared to the performance of an unplanted but otherwise identical prototype. The thermal performance was analysed by observing the temperature variation simultaneously in a non-vegetated and vegetated structure. The initial findings show that the combination of green roof and green walls have a relevant role in temperature attenuation. These results indicate, that this lightweight retrofit green technology could not only represent an important advance on sustainable development, but can that it also lead to more comfortable internal conditions for humans living in dense urban environments.